THE TRUTH THAT SHAHRIZODA SAID - Aminovna, Astanova Gulnora (International Journal of Psychosocial Rehabilitation, 2020)
In the stories of the work "one Thousand and one nights", the image of women of different categories is perfectly expressed in bright styles. Eastern qualities, such as beauty, delicacy, and charm ge of a woman who embodied the virtues of wisdom, enterprise, and prudence, gave luster to the charm of the work. This article provides a scientific analysis of myths and legends, which show the above-mentioned features in the image of women mentioned by Shakhrizoda in the work "one Thousand and one nights". The paper presents scientific hypotheses that the meaning and purpose of highlighting such a female image is the presence of a prototype in life. The article examines the wise and enterprising Eastern women in life by comparing them in which Shahrezada tells the story in the work. The problems of influence of enterprising Eastern women on the image of a woman in the work "one Thousand and one nights"are investigated.